2017
DOI: 10.1038/s41598-017-09488-4
|View full text |Cite
|
Sign up to set email alerts
|

Achievability of 3D planned bimaxillary osteotomies: maxilla-first versus mandible-first surgery

Abstract: The present study was aimed to investigate the effects of sequencing a two-component surgical procedure for correcting malpositioned jaws (bimaxillary osteotomies); specifically, surgical repositioning of the upper jaw—maxilla, and the lower jaw—mandible. Within a population of 116 patients requiring bimaxillary osteotomies, the investigators analyzed whether there were statistically significant differences in postoperative outcome as measured by concordance with a preoperative digital 3D virtual treatment pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…With respect to our previous study 4 , which investigated the effects of sequencing bimaxillary osteotomies (maxilla-first versus mandible-first) on the achievability of the 3D virtually planned bimaxillary surgeries, it can be concluded that the sequence of surgery is more of clinical importance to the achievability of the 3D virtually planned repositioning of the jaws, rather than the stability of the achieved postoperative results. It is the surgeon’s choice to choose the most suitable sequence of bimaxillary osteotomies in each individual case.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…With respect to our previous study 4 , which investigated the effects of sequencing bimaxillary osteotomies (maxilla-first versus mandible-first) on the achievability of the 3D virtually planned bimaxillary surgeries, it can be concluded that the sequence of surgery is more of clinical importance to the achievability of the 3D virtually planned repositioning of the jaws, rather than the stability of the achieved postoperative results. It is the surgeon’s choice to choose the most suitable sequence of bimaxillary osteotomies in each individual case.…”
Section: Discussionmentioning
confidence: 85%
“…The clinical cohort consisted of patients who underwent bimaxillary osteotomies at Radboud University Medical Centre between 2010 and 2014 (n = 116) 4 . In this one-year follow-up study, data from 106 patients (n = 73 female (69%); n = 33 male (31%); mean age 28 (range 16–57; Table 1)) were analysed to determine the level of skeletal relapse after undergoing either maxilla-first (n = 53) or mandible-first (n = 53) bi-maxillary surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another reason for the larger discrepancies in the impaction-elongation direction and pitch orientation might be caused by the bony interferences between the pterygoid plates and the posterior part of the osteotomized maxilla [41]. This could lead to deviations in the impaction-elongation direction and pitch orientation, as it is difficult to visually check the bony interferences during surgery [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Once a surgical plan has been formulated, virtual osteotomies are made. Maxilla-first surgery has been shown to be more predictable, except where the maxilla and mandible are both being rotated counter-clockwise, where mandible-first surgery is more predictable (Liebregts et al, 2017).…”
Section: D-vsp Protocol For Orthognathic Surgerymentioning
confidence: 99%